Social and occupational factors associated: Life time prevalence of low back pain in primary care [Bi̇ri̇nci̇ basamakta yaşam boyu bel aǧrisi sikliǧi ve i̇li̇şki̇li̇ sosyal ve mesleksel ri̇sk etmenleri̇] - (:unkn) unknown (My University, 2010)
Introduction: This study aims to determine the prevalence of life-time low back-pain and affecting occupational and social risk factors, in primary health care. Methods: A total of 2287 subjects (82,7%), aged 15 and over who has attended to five primary health care centers in the training and research district of Gazi University Department of Public Health in July- August 2005 and accepted to answer the questionnaire, participated in the study. Socio-demographic characteristics, working conditions, low back pain prevalence and some possible risk factors have been evaluated for the participants. Data has been processed by using SPSS 11.5 (Chicago, Il, USA) statistical programme. T-test was used for continuous variables and chi-square test for categorical variables. Results were presented with 95% Confidence Interval (CI) s, p values less than 0.05 was considered as statistically significant. Results: The mean age of the participants was 39.0±14.9 (15-86). %31.8 was male, %92.3 had social insurance, and 47.5% of them were housewives. The life-time low back pain prevalence was found to be 79.4%. LTBP risk was higher in person who was older, had higher BMI, experienced economic problems, was shorter and had lower educational level. And heavy-lifting, frequent bending up-rising and standing for long time was determined as occupational risk factors. LTBP risk was increased in workers and house-wives and decreased in person making sport for one hour a week. Conclusion: Life-time low back pain prevalence was considerably high among the study group. The determination of the risk factors and provision of necessary preventive approaches will decrease the prevalence of low back pain which is a prevalent health problem among community.
Keywords: Low back pain; Occupation; Prevalence; Risk factors